Inflammasome Signaling and Impaired Vascular Health in Psoriasis. Issue 4 (April 2019) - Garshick, Michael S.; Barrett, Tessa J.; Wechter, Todd; Azarchi, Sarah; Scher, Jose U.; Neimann, Andrea; Katz, Stuart; Fuentes-Duculan, Judilyn; Cannizzaro, Maria V.; Jelic, Sanja; Fisher, Edward A.; Krueger, James G.; et al.
Abstract : Objective—: Psoriasis is an inflammatory skin disease which heightens the risk of cardiovascular disease. This study directly investigated vascular endothelial health and systemically altered pathways in psoriasis and matched controls. Approach and Results—: Twenty patients (mean age, 40 years; 50% male) with active psoriasis and 10 age-, sex-matched controls were recruited. To investigate systemically alerted pathways, a deep sequencing omics approach was applied, including unbiased blood transcriptomic and targeted proteomic analysis. Vascular endothelial health was assessed by transcriptomic profiling of endothelial cells obtained from the brachial veins of recruited participants. Blood transcriptomic profiling identified inflammasome signaling as the highest differentially expressed canonical pathway ( Z score 1.6; P =1×10 -7 ) including upregulation of CASP5 and interleukin ( IL ) -1β . Proteomic panels revealed IL-6 as a top differentially expressed cytokine in psoriasis with pathway analysis highlighting IL-1β ( Z score 3.7; P =1.02×10 -23 ) as an upstream activator of the observed upregulated proteins. Direct profiling of harvested brachial vein endothelial cells demonstrated inflammatory transcript (eg, IL-1β, CXCL10, VCAM-1, IL-8, CXCL1, Lymphotoxin beta, ICAM-1, COX-2, and CCL3 ) upregulation between psoriasis versus controls. A linear relationship was seen between differentially expressed endothelial inflammatory transcripts and psoriasis disease severity. IL-6 levels correlated with inflammatory endothelial cell transcripts and whole blood inflammasome-associated transcripts, including CASP5 and IL-1β . Conclusions—: An unbiased sequencing approach demonstrated the inflammasome as the most differentially altered pathway in psoriasis versus controls. Inflammasome signaling correlated with psoriasis disease severity, circulating IL-6, and proinflammatory endothelial transcripts. These findings help better explain the heightened risk of cardiovascular disease in psoriasis. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT03228017. Abstract : Supplemental Digital Content is available in the text.